Gastrointestinal intraluminal pH in normal subjects and those with colorectal adenoma or carcinoma. Issue 12 (December 1990) - Pye, G; Evans, D F; Ledingham, S; Hardcastle, J D
Abstract : Recent evidence suggests that the production of colorectal carcinogens is facilitated when the pH of the colonic contents is alkaline. It follows that the colonic intraluminal pH of patients with colorectal neoplasms should be higher than in normal subjects. Gastrointestinal pH has been measured in 30 patients with colorectal cancer and 37 patients with benign colorectal adenomas (using a pH sensitive radiotelemetry capsule). These values have been compared with those recorded in 66 normal subjects. No differences in gastrointestinal pH were found and the results did not support the hypothesis that colonic pH plays a role in the aetiology of colorectal neoplasia.